The Associated Factors of The Inpatient Medical Records Quality in RSUD DR. Moewardi Surakarta - Priaji Setiadani; Endang Sutisna Sulaeman; Penggalih Mahardika Herlambang (Nexus Kedokteran Komunitas, 2016)
Background: One components of the quality of health care which is given by hospitals is the availability of data or information from the medical record. According to Permenkes 269 of 2008 concerning medical records, recording of patient data is a compulsion, and a legal obligation. Methods: This research is a non-experimental descriptive study. The design of the study uses a cross-sectional. This research was conducted in the inpatient medical record installation of RSUD DR Moewardi Surakarta. The researchs method is a combined method approach (mixed methods) that combines qualitative and quantitative approaches. A qualitative approach is as the primary while the quantitative approach plays as a support. Samples were taken in purposive sampling, is the five informants as medical records executant. Data collected through in-depth interviews, observation, and analysis of documents. Qualitative data analysis is done through a tangle analysis and interactive analysis, while quantitative data were collected and analyzed by using a check list to determine the output quality of medical records. Results: The associated factors of the medical records quality of inpatients in RSUD DR Moewardi are the input, processes and the output of medical records. Input include energy, funds, materials, machines, methods, socialization, time and information. Process include the implementation process when the medical records in medical services and medical records at the time of file handling, namely the processing, storage, lending, and the return of the medical record file. Output include stuffing completeness, accuracy, timely refund, and compliance aspects of the legal requirements. The result of the total quality of medical records was 93.05%. The qualities of the medical records are categorized as good. Conclusion: The associated factors of the medical records quality of inpatients in RSUD DR Moewardi are the input factors, process factors and the output factors. Input factors are workforce factors, fund factors, material factors, engineering factors, methods factors, socialization factors, the time factor, information factors. Process factors include the implementation process when the medical records in medical services and medical records at the time of file handling, namely the processing, storage, lending, and the return of the medical record file. Output factors include stuffing completeness, accuracy, timely refund, and compliance aspects of the legal requirements. Keywords: medical records, medical records quality.